Analysis of proteins by capillary electrophoresis with a novel diazoresin/β-Cyclodextrin covalent capillary coating method. (26th July 2020) - Xing, Jie; Wang, Ming-Hong; Wang, Song; Cong, Hai-Lin; Shen, You-Qing; Yu, Bing
Abstract: In this paper, we report on a successful development and application of diazoresin (DR)/β-Cyclodextrin covalently linked capillary coatings using the layer by layer (LBL) self-assembly technique combined with photochemistry reactions. The modified capillary remarkably suppressed the protein adsorption on the inner surface of silica capillary and successfully separated lysozyme (Lys), myoglobin (Mb), bovine serum albumin (BSA) and ribonuclease A (RNase A). Furthermore, the DR/β-Cyclodextrin covalently linked capillary coatings showed good stability and repeatability. More importantly, this method is more environmentally friendly and simpler than traditional methods for the use of DR instead of highly toxic and moisture-sensitive silane coupling agent.